PTU-024 Reliability of Rockall Score Calculation and its Impact on Gastroscopy in Patients with Acute upper Gastrointestinal Bleed (Augib). (4th June 2013) - Taranath, A; Gupta, S; Mallick, S
Abstract : Introduction: Documentation of Rockall score (RS) in patients with AUGIB should be accurate to prioritise patients for gastroscopy. We noticed that Rockall scores were being incorrectly calculated on electronic gastroscopy request forms and decided to analyse this further. We correlated RS with findings on gastroscopy Methods: Information was retrospectively collected on 100 patients who presented with AUGIB over a 2 month period between September and November 2012. Demographics, time to gastroscopy, Rockall score (RS) documented by requesting doctor, RS calculated by going through patient records (including A & E, paramedic entries) were recorded. We analysed patients whose RS was either under scored or over scored by the requesting doctor (as compared to the actual score as calculated by us) and correlated this with the electronic endoscopic records Results: 100 patients were included in the study with 60 males (60%) and 40 females (40%), age ranging from 17 to 92, (mean 65.2, median 69.5). Presenting symptoms were melaena in 57% of patients, haematemesis in 27%, coffee grounds vomiting in 12% and combined melaena and haematemesis in 4%. RS was calculated in 52% by Foundation Year 1 trainees (FY1), in 10% by FY2s, in 26% by Senior House officers (SHO), in 6% by Locum SHOs, in 5% by Registrars and in 1% by a consultant. 46 out of 100 Rockall scores were incorrectly scored. 28 patients (60.9%) were over scored, while 18(39.1%) were underscored FY1s were responsible for incorrect scores in 27(58.7%) of patients, FY2 for 2 (4.3%), SHOs for 12(26%), locum SHOs for 3(6.5%) and registrars for 2(4.3%). Mean time from electronic booking to endoscopy was days in patients Mean time to Gastroscopy was day in of under scored patients day in of over scored patients. Of the 18 patients whose RS was under scored, 6 (33.3%) required endoscopic intervention with heater probe and Adrenalin injection. Of the 28 patients whose RS was over scored, only 3(10.7%) needed endoscopic intervention, while 5 of the 54 (9.2%) of the correctly scored patients needed endoscopic therapy. Conclusion: It is important to calculate the RS correctly at the time of first presentation rather than at the time when the admitting doctor sees the patient. Observations from A&E and ambulance records should be scrutinised to document the accurate RS thus helping endoscopy units to correctly prioritise patients for gastroscopy. Incorrect calculation of RS can have adverse impact on patient outcomes – under scored patients may be delayed while over scored patients may use up vital endoscopy slots. Disclosure of Interest: None Declared